Hollywood and the Military Bureaucracy: Depicting America's Fighting Forces at Their Best and Worst - Herzberg, Bob (MCFARLAND & CO INC, 2021)
Through a century of movies, the U.S. military held sway over war and service-oriented films. Influenced by the armed forces and their public relations units, Hollywood presented moviegoers with images of a faultless American fighting machine led by heroic commanders. This book examines this cooperation with detailed narratives of military blunders and unfit officers that were whitewashed to be presented in a more favorable light. Drawing on production files, correspondence between bureaucrats and filmmakers, and contemporary critical reviews, the author reveals the behind-the-scenes political maneuvers that led to the rewriting of history on-screen.
https://katalog.adlr.link/Record/51-9781476678481